Time Blind : Problems in Perceiving Other Temporalities - Birth, Kevin K. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores how modern concepts of time constrain our understanding of temporal diversity. Time is a necessary and pervasive dimension of scholarship, yet rarely have the cultural assumptions about time been explored. This book looks at how anthropology--a discipline known for the study of cultural, linguistic, historical, and biological variation and differences--is blind to temporalities outside of the logics of European-derived ideas about time. While the argument focuses primarily on anthropology, its points can be applied to other fields in the sciences, humanities, and social sciences. .